KAZAKH HISTORICAL EPICS AND EPICAL TRADITION - KABDESHOVA, K.; RAKYSH, ZH; AUYESBAYEVA, P.; ALBEKOV, T.; ALPYSBAYEVA, K. (Utopía y Praxis Latinoamericana, 2019)
ABSTRACT Historical epics have great significance in world literature. Kazakh historical epics were created by folk poets. In the study, authorial historical epics are compared with heroic poetry and historical epics. In the narrative, common motives are defined between the historical epics by folk poets and the heroic poetry; the attributes are listed differentiating the former from the heroic epics. The subject of this research is the historical epics made by folk poets, their place in the Kazakh literature, the ancient motives, epical traditions in the structure, plot of compositions of this category.RESUMEN Las epopeyas históricas tienen un gran significado en la literatura mundial. Las epopeyas históricas kazajas fueron creadas por poetas populares. En el estudio, las epopeyas históricas de autor se comparan con la poesía heroica y las epopeyas históricas. En la narrativa los motivos comunes se definen entre las epopeyas históricas de los poetas populares y la poesía heroica, se enumeran los atributos que diferencian a las primeras de las epopeyas heroicas. El tema de esta investigación son las epopeyas históricas hechas por poetas populares, su lugar en la literatura kazajo, los motivos antiguos, las tradiciones épicas en la estructura, la trama de composiciones de esta categoría.